2019
DOI: 10.4236/ijohns.2019.84015
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Malignancy in Solitary Thyroid Nodule in a Tertiary Level Hospital of Bangladesh

Abstract: Objectives: To determine the frequency of thyroid malignancy in clinically and sonographically solitary thyroid nodule in patients undergoing thyroidectomy in Comilla Medical College Hospital. Methods: A cross sectional study was carried out at the Department of Otolaryngology and Head Neck Surgery of Comilla Medical College Hospital during the period from January 2016 to January 2019. This study includes all patients admitted and undergoing surgery with solitary thyroid nodule. Results: Out of 188 patients 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…12 A cross sectional study done in Bangladesh gave results that among 188 study subjects 24 found with histologically thyroid malignancy. 13 A study which was performed on 141 patients with true solitary thyroid nodules undergoing bilateral total thyroidectomy reported irregular borders, microcalcification, increased vascularity, and detection of cervical lymphadenopathy were found to be correlated with malignancy in solitary nodules. 14 Present study gave us finding that 68% of population had benign lesions incidence with solitary thyroid nodule.One study showed that Solitary Nodule of Thyroid was more common in female participants with incidence of Malignancy of 8%.…”
Section: Discussionmentioning
confidence: 99%
“…12 A cross sectional study done in Bangladesh gave results that among 188 study subjects 24 found with histologically thyroid malignancy. 13 A study which was performed on 141 patients with true solitary thyroid nodules undergoing bilateral total thyroidectomy reported irregular borders, microcalcification, increased vascularity, and detection of cervical lymphadenopathy were found to be correlated with malignancy in solitary nodules. 14 Present study gave us finding that 68% of population had benign lesions incidence with solitary thyroid nodule.One study showed that Solitary Nodule of Thyroid was more common in female participants with incidence of Malignancy of 8%.…”
Section: Discussionmentioning
confidence: 99%